(3GdJLGQI GdGdcJQhfjI h JCejfgG (B/s - (3MSjf, aGQhb SjOs ((3eUQ(B: s (3gdG ddfTQ (B, s, 2001)
(3jJfGhd GdcJGH GdGef , fXGe GdOaY GdGdcJQhfj ,NOeGJ Cef GdOaY ,GWGQ GdOaY GdGdcJQhfj , Gef WHbI GdJWHjb , HQhJhchdGJ fbd ZjQ JJGHYj , Gef NGOe GdTHcI , eaGgje GdJLGQI GdGdcJQhfjI eDSSI Ydi GdTHcI , Gef GdeMehd, Gef GdHWGbI GdPcjI (B.s
Keywords: (3GdHWGbI GdPcjIs; (3GdJLGQI GdEdcJQhfjIs; (3GdOaY GdGdcJQhfjs